Aspectos fiscais quanto à possibilidade de unificação monetária no Mercosul: uma análise do déficit e da dívida pública à luz da experiência européia - Londero, Daiane (2008)
This work presents an analysis of the fiscal character of the Monetary Unification for Mercosul, based on the Euro experience. To do so, the ratings of debt and public deficit are checked out, aiming to discover the possibilities of the creation and maintenance of a Mercosul’s Monetary Union in European frames. In European case, the Stability and Growth Pact was signed, aiming to get a solid management of public finances, creating, therefore, fiscal rules that set boundaries to the deficit and the debt. Meanwhile, the hypothesis of a "Mercosul’s Stability and Growth Pact" is considered, verifying, through instruments such as the Contract Theory and the Theory of Games, the possibility of future maintaining of a hypothetical single currency in Latin-American region. Thus, the present work is divided as follows: after an introduction of the subject, a first chapter presents notions of economic integration, as well as monetary union, through theoretical and practical considerations and parallel between European Union and Mercosul; in a second moment, the criterion that make possible the creation of a single monetary area, specially in what concerns to the debt and the deficit, are analyzed; in the third chapter, the maintaining of the monetary union after its consolidation is approached, through the proposition of a "Mercosul’s Stability and Growth Pact” in European frames; finally, some conclusions are presented.